2021
DOI: 10.1049/cds2.12081
|View full text |Cite
|
Sign up to set email alerts
|

CMOS X‐band pole‐converging triple‐cascode LNA with low‐noise and wideband performance

Abstract: A pole-converging X-band low-noise amplifier (LNA) using 130 nm CMOS technology is proposed. An on-chip pole-converging capacitor C PC is added between the gate and drain node of the common-gate (CG) stage. The capacitor C PC combines with a noisereducing inductor L 1 to converge poles into the desired band, which results in a poleconverging effect and wideband performance. The proposed modified broadband simultaneous noise and input-matching technique is adopted in triple-cascode configuration to realize good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, the gate‐to‐source and gate‐to‐drain capacitances are degraded by 4% and 36%, respectively that reduced the speed of the input stage. Cheng Cao et al 28 suggested a CMOS pole‐converging triple‐cascode LNA in which a pole‐converging capacitor is integrated between the gate and drain node of the common‐gate stage and resulted in a pole‐converging effect and wideband performance. The altered broadband simultaneous noise and input‐matching technique was employed in triple‐cascode configuration to realize good input matching and a low NF.…”
Section: Literature Surveymentioning
confidence: 99%
“…However, the gate‐to‐source and gate‐to‐drain capacitances are degraded by 4% and 36%, respectively that reduced the speed of the input stage. Cheng Cao et al 28 suggested a CMOS pole‐converging triple‐cascode LNA in which a pole‐converging capacitor is integrated between the gate and drain node of the common‐gate stage and resulted in a pole‐converging effect and wideband performance. The altered broadband simultaneous noise and input‐matching technique was employed in triple‐cascode configuration to realize good input matching and a low NF.…”
Section: Literature Surveymentioning
confidence: 99%
“…There have been recent reports for designing and fabricating GaAs‐based LNAs, 3–5 switches, 6,7 and multiphase clock generators, 8 using 0.15 and 0.25 μm technology. LNAs based on other competitive technologies, CMOS, 9–13 and SiGe BiCMOS 14,15 have also been reported in the literature recently. CMOS technology has the advantage of high integration density and low cost, 16 whereas GaAs 1 and SiGe 17 have better noise performances.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar and Rebeiz 9 have proposed X‐ and K‐band LNAs with a method of noise match optimization with respect to the base inductor in a 0.18 μm SiGe HBT technology. Cao et al 12 have proposed a pole converging technique to improve the noise figure (NF) over a broad range from 8 to 12 GHz using 0.13 μm CMOS technology. Zailer et al 13 have demonstrated a method based on transistor size selection, that is, Cgs and simultaneous bias, to minimize the difference between NF and NF min using 0.13 μm CMOS inductive source degenerated (ISD) cascode LNA.…”
Section: Introductionmentioning
confidence: 99%